1970
DOI: 10.1161/01.res.27.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Regression of Coronary Atheromatosis in Rhesus Monkeys

Abstract: Rhesus monkeys subjected to the atherogenic stimulus of a high-fat, high-cholesterol diet showed significant coronary atheromatosis at the end of 17 months. Smaller fibrotic lesions with scant stainable lipid were found in animals that were subsequently fed either of two cholesterol-free diets for 40 months. The average cross-sectional area of the lumen was more than 80% greater in regression animals than in monkeys with baseline atherosclerosis. The data support the hypothesis that uncomplicated coronary athe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
1
4

Year Published

1973
1973
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 356 publications
(68 citation statements)
references
References 17 publications
2
61
1
4
Order By: Relevance
“…Daoud et al (1976)presented a convincing report of the regression of advanced atheroma in swine, but these authors used a very long (14-month) regression period. Similarly, Armstrong et al (1970Armstrong et al ( , 1972 reported the regression of elevated lipid-rich experimentally induced atherosclerotic lesions in the rhesus monkey after changing to a low-fat or corn-oil enriched, low-cholesterol diet. Here there was a 40-month regression period.…”
Section: Discussionmentioning
confidence: 96%
“…Daoud et al (1976)presented a convincing report of the regression of advanced atheroma in swine, but these authors used a very long (14-month) regression period. Similarly, Armstrong et al (1970Armstrong et al ( , 1972 reported the regression of elevated lipid-rich experimentally induced atherosclerotic lesions in the rhesus monkey after changing to a low-fat or corn-oil enriched, low-cholesterol diet. Here there was a 40-month regression period.…”
Section: Discussionmentioning
confidence: 96%
“…Rhesus atherosclerotic monkeys were fed a semipurified atherogenic diet 28 that contained 41% of the total calories as fat and 1.2% cholesterol. The cynomolgus atherosclerotic monkeys were fed the same atherogenic diet except that the cholesterol content was fj.8%.…”
Section: Animalsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Morphometry of cross sections can accurately quantify lesion area and volume but is too labor intensive to determine atherosclerosis in larger arterial segments or in the entire aorta. Planimetry does not measure lesion volume and, therefore, is insensitive to the progression of fatty streaks to advanced lesions.…”
mentioning
confidence: 99%